Neighborhood socio-economic context and emergency department visits for dental care in a U.S. Midwestern metropolis. Issue 3 (March 2015) - Hong, L.; Liu, Y.; Hottel, T.L.; Hoff, G.L.; Cai, J.
Abstract: Objective: This study was to examine the association between emergency department (ED) visits for dental complaints and neighborhood socio-economic contexts of patients in a U.S. Midwestern metropolis. Study design: A retrospective study. Methods: Deidentified data of ED visits for the period 2001–2010 from all facilities serving Kansas City, Missouri and 2007–2011 American Community Survey 5-Year Estimates data were used to determine odds of visit by neighborhood socio-economic characteristics at the ZIP code level. ED visits with diagnoses of International Classification of Disease 9th Revision codes related to toothache or tooth injury were included. ZIP code characteristics included percent of non-white population, median family income, percent of population 25 years and older with at least a high school degree, and percent of population with a language other than English spoken at home. Each ZIP code characteristic was divided into quartiles. Chi-square tests and two-level hierarchical linear modeling (HLM) were conducted. In the HLM, the outcome variable was whether to have an ED visit for dental complaints (yes/no), the first-level variables were characteristics of individual ED visits, and the second-level variables were ZIP code characteristics. Results: The study population made 1, 786, 939 ED visits, of which 35, 136 (1.9%) were for dental complaints. Among the patients making ED visits for dental complaints, 54.8% were female, 51.9% were younger adults aged 19–35 years, 48.7% were non-Hispanic black, and 35.5% used self-pay as the source of payment. After controlling the first-level variables, the HLM showed that the risk of ED visits for dental complaints significantly increased for individuals residing in ZIP Code Tabulation Areas with lower median family income, or a higher proportion of the population with a language rather than English spoken at home. Conclusions: Among socio-economic characteristics examined, median family income and percent of population with a language other than English spoken at home are important indicators of ED visits for dental complaints.